Making sense of the unfeasible : my life journey with Asperger Syndrome - Fleisher, Marc, 1967- (Jessica Kingsley, 2003)
Before he received his diagnosis of Asperger Syndrome (AS) in the 1970s, Marc Fleisher was considered mentally retarded; yet he went on against the odds to gain two maths degrees and to undertake post-graduate studies in maths. In this engaging story Marc relates how, supported by his family and by services for people with autism, and despite family tragedy and personal difficulties, he learnt to get the most out of life. He shares, with humour and candour, a multitude of practical tips for people with AS, and those around them, rounding off his story with appendices on astronomy, parallel uni.